Kebijakan Perlindungan Hukum Kawasan Suci Pura Goa Lawah Di Kabupaten Klungkung - Manuaba, Ida Bagus Triwikrama Sena; Wisnumurti, Anak Agung Gede Oka; Arjaya, I Made (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This thesis research analyzes the Legal Protection Policy of the Sacred Area of Goa Lawah Temple in Klungkung Regency. The focus of this research study is about (1) what is the policy of the Klungkung Regency Government in protecting the sacred place area? (2) how is law enforcement against violations of space use in the area of the sacred site of Goa Lawah Temple, Klungkung Regency? The type of research used is empirical by choosing the type of research with the aim of finding out the legal protection policy of the sacred site area in Klungkung Regency and how to enforce violations of space use in the Goa Lawah temple holy area. The author examines with the theory of legal certainty, the theory of the legal system and the theory of law enforcement, from the three analysis knives the author produces the conclusion (1) With the rapid expansion of the tourism sector, Klungkung Regency faces great challenges to carry out spatial planning, so the Klungkung Regency Government issued a policy in the form of a Regional Regulation on the protection of the sacred place area, in Regional Regulation Number 1 of 2024 concerning the Klungkung RTRWK, The Regional Regulation is a form of protection of sacred sites in Klungkung Regency (2) law enforcement in spatial planning in the form of supervision and the application of sanctions in Regional Regulation Number 1 of 2024 RTRWK Klungkung and Law Number 26 of 2007 concerning Spatial Planning dividing it into administrative, civil, and criminal.